At-Taḥlīl 'an Ḍa'fi Dāfi'iyyat Ta'allum al-Lughah al-'Arabiyyah li Ṭullāb al-Ṣaff al-Thānī 'Ashar bi al-Madrasah al-'Āliyah al-Ḥukūmiyyah al-Islāmiyyah Tabanuli al-Shamāliyyah - Sikni Sari Siagian; Khoirul Jamil (Al Maghazi : Arabic Language in Higher Education, 2026)
Learning motivation is one of the key factors determining the success of Arabic language learning in madrasahs. However, previous studies have indicated that students' motivation to learn Arabic remains at a low to moderate level, as reflected in limited classroom participation, low learning interest, and a lack of confidence in learning Arabic. This study aims to analyze the low level of Arabic learning motivation among twelfth-grade students at Madrasah Aliyah Negeri Tapanuli Utara and to identify the factors influencing it. This research employed a qualitative approach using a descriptive research design. The participants consisted of twelfth-grade students, Arabic language teachers, and school administrators. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. Data credibility was ensured through source and technique triangulation. The findings reveal that students' low motivation to learn Arabic is influenced by internal factors, including low learning interest, negative perceptions of Arabic, and a lack of self-confidence, as well as external factors such as limited variation in teaching methods, inadequate learning media, and students' perceptions that Arabic has limited relevance to their academic and future career needs. It can therefore be concluded that low motivation in learning Arabic results from the interaction between internal and external factors. This study contributes empirical evidence to the literature on Arabic language learning motivation at the senior Islamic secondary school level and provides a basis for developing more contextual, innovative, and learner-centered instructional strategies. Future research is recommended to investigate the effectiveness of various instructional interventions in enhancing students' motivation to learn Arabic across different educational contexts.